Self-discharge rates in cells have a critical effect on the cycle life of parallel lithium-ion batteries. Issue 54 (31st August 2018) - An, Fuqiang; Zhao, Hongliang; Li, Ping
Abstract : More than two parameters are adopted to sort lithium ion cells (LICs) for better performance in the production process, such as capacity, open-circuit voltage (OCV), direct current resistance (DCR), et al. Abstract : More than two parameters are adopted to sort the lithium ion cells (LICs) for better performance in the production process, such as capacity, open-circuit voltage (OCV), direct current resistance (DCR), et al. However, more sorting parameters make mass production more complex. In order to solve this conflict, we compare capacity, OCV, DCR, and self-discharge rate ( k OCV ) in this paper, investigate their different effects on the cycle life of parallel LICs through analyzing the relationship between component cell variations and the durability of the parallel blocks. We find that the variations of the self-discharge rate in cells significantly affect the discharge capacity retention of the blocks: bigger variation in the cells results in a better cycle life of parallel LICs. Thus, it is prudent to perform cell sorting for the assembly of superior blocks based on the self-discharge rates of the cells.